Mediastinal Hodgkin lymphoma arising from cystic lymphangioma: case report in a child - Büyükkapu-Bay, Sema; Çorapcıoğlu, Funda; Gürkan, Berra; Erçin, M. Cengiz; Anık, Yonca; Karadoğan, Meriban (The Turkish Journal of Pediatrics, 2012)
Mediastinal disease is a frequent clinical presentation in children with Hodgkin lymphoma. It is usually due to mediastinal lymphadenopathy or involvement of the thymus gland. Cystic lymphangiomas are benign tumors of the lymphatic system, and less than 1% present as a solitary mediastinal mass. To our knowledge, there has been no report in the literature describing Hodgkin lymphoma arising from cystic lymphangioma. In this report, we describe a patient with mediastinal cystic lymphangioma, from which Hodgkin lymphoma was determined to have arisen.